Metaphysics : the elements - Aune, Bruce, 1933- (University of Minnesota Press, 1985)
A comprehensive introductory study of the key concepts and problems in traditional and contemporary metaphysics. Aune presents and defends a point of view that is naturalistic, nominalistic and pragmatic-an approach that has the overall advantage of providing a coherent, structured view of the topics he discusses.